The 'sacrifice' of human rights during an unprecedented pandemic: Reflections on survey-based evidence. Issue 2 (3rd April 2021) - Bohler-Muller, Narnia; Roberts, Benjamin; Gordon, Steven Lawrence; Davids, Yul Derek
Abstract: Twenty-five years into our constitutional democracy the Covid-19 pandemic led President Ramaphosa to declare a state of national disaster in terms of the Disaster Management Act 57 of 2002 (DMA). Strict lockdown regulations promulgated under the DMA had a clear bearing on human rights, such as the rights of religious observance, assembly and demonstration, association, movement, trade, and education. In the case of De Beer v Minister of Cooperative Governance and Traditional Affairs (2020), the High Court declared some of the regulations promulgated under lockdown levels four and three irrational and thus unconstitutional. Yet the question we ask is, do ordinary South Africans support the limitation of their rights? To provide insight we analyse data from the University of Johannesburg and Human Sciences Research Council (UJ/HSRC) Covid-19 Democracy Survey, which was administered using a data free mobile platform from April 2020 to January 2021. Over three survey rounds, the willingness to sacrifice human rights remained high. Throughout the pandemic, the role of public opinion has been largely overlooked. The Covid-19 Democracy Survey served as one way to facilitate democratic participation as it allowed people to express their views, opinions and concerns about the virus and living under lockdown. This article discusses human rights 'sacrifice' in the specific context of this pandemic. It is argued that limiting certain constitutionally protected freedoms discussed herein may be necessary during a national disaster to 'flatten the curve' and protect oneself and others, but that careful attention should be paid to non-discrimination, dignity and the temporary nature of rights limitations.